التطهير المستمر لهواء حظائر الدواجن أثناء وجود الطيور كإجراء لخفض مستوى الحمولة الجرثومي والوقاية من الأمراض - عبد العزيز, فهيم; نيصافي, علي (Latakia University Journal -Biological Sciences Series, 2019)
لتحقيق الأمن الحيوي الفعال وحماية الدواجن من المخاطر التي تتعرض لها صناعة الدواجن في ظل الرعاية المكثفة والإنتاج المرتفع الذي يشهده هذا القطاع, تم اختبار مدى فاعلية مزيج من مركبات يودور البوتاسيوم واليود وثلاثي إيتيلين الغليكول في خفض الحمولة الجرثومية في هواء حظائر الدواجن ( بياض ولحم ) أثناء وجود الطيور في فترات الرعاية أو الإنتاج باستخدامه بالطريقة الرذاذية وبجرعة5 مل/م3 ومدى انعكاس ذلك إيجابياً على الحالة الصحية والإنتاجية للطيور. بينت النتائج انخفاض كثافة الجراثيم مابين(15-10) ضعفا وتدني نسبة النفوق إلى 3% بسبب انحسار الإصابة بالأمراض, وارتفاع مردود اللحم بنسبة 3,5% بالمقارنة مع المزرعة الشاهدة . To achieve effective biosecurity and poultry protection in the conditions of intensive rearing and high production that are being witnessed by this industry and the increasing risks facing it, a combination of Potassium iodide, Iodine, and Triethyline glycol compounds with spray method and a 5ml/m³ dose was used in fowl barns (both egg and meat production) while the birds were rearing or producing, where the combination's effectiveness in reducing microbiological load and the extent to which that was positively reflected in the healthy condition and production of the birds was tested. The laboratory study recorded a 10-15 times reduction in bacterial intensity. The field observations also showed a reduction in disease infections and a decrease in the rate of fatalities by 3% and an increase in meat yield by about 3.5% in comparison with the control farm.